Metabarcoding assessment of fungal diversity in brown algae and sponges of Mauritius - Wong Chin, Jessica Mélanie; Puchooa, Daneshwar; Bahorun, Theeshan; Neergheen, Vidushi S.; Aullybux, Aadil Ahmad; Beedessee, Girish; Nazurally, Nadeem; Alrefaei, Abdulwahed Fahad; Jeewon, Rajesh (Frontiers in Microbiology, 2022)
Marine fungi are largely associated with important inhabitants of the marine ecosystem such as sponges and algae. They are important colonisers and play vital ecological roles such as nutrient cycling, organic matter decomposition and symbiosis with other organisms. High throughput sequencing methods have been used successfully to reveal unknown fungal communities associated with a number of hosts particularly in the marine environment. However, the diversity of marine fungi associated with sponges and brown algae in Mauritius remains largely unknown. Traditional methods based on culturing do not provide reliable estimate of fungal diversity as only those that are able to grow under laboratory conditions are dominant; in addition, a large proportion of fungal microorganisms, cultured in vitro remain unidentifiable, given that there are no sporulating structures to be examined morphologically. To overcome these limitations, we employed Illumina sequencing to unravel fungi species present in the sponges, Iotrochota sp. and Biemna sp. and the brown algae Turbinaria conoides, Sargassum pfeiffereae and Sargassum obovatum, collected from the north of Mauritius. Diversity analyses revealed that Biemna sp. had the highest diversity from the sampled sponges with fungi from 24 orders being recovered while from brown algae, Turbinaria conoides had the highest diversity with recovery of fungal taxa of the orders Mucorales, Eurotiales, Botryosphaeriales, Chaetothyriales and Hypocreales, with the latter four orders being common in both sampled algae and sponges. Beta diversity analyses revealed clustering only in the algae, Turbinaria conoides, and Sargassum pfeiffereae and not in the co-occurring sponges, indicating that sampling location did not have much influence on fungal diversity. Our findings provide the first amplicon sequencing based insights of the fungal communities associated with macro-algae and sponges in Mauritius and supplements research on the fungal community existing in the oceans around the world.